2022
DOI: 10.1186/s12951-022-01402-z
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation engineered nanogold for multimodal cancer therapy and imaging: a clinical perspectives

Abstract: Cancer is one of the significant threats to human life. Although various latest technologies are currently available to treat cancer, it still accounts for millions of death each year worldwide. Thus, creating a need for more developed and novel technologies to combat this deadly condition. Nanoparticles-based cancer therapeutics have offered a promising approach to treat cancer effectively while minimizing adverse events. Among various nanoparticles, nanogold (AuNPs) are biocompatible and have proved their ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 210 publications
(204 reference statements)
0
11
0
1
Order By: Relevance
“…39 As an alternative option, metal-based nanomaterials, especially high-Z materials (eg, Au, bismuth, platinum, gadolinium), have been used in experimental and clinical applications as common radiosensitizers. [40][41][42] Owing to the emission of low-energy photoelectrons and the interaction of Auger electrons, high-Z nanomaterials can absorb, scatter, and eradicate radiation energy. Moreover, when compared with other metal-based nanomaterials, Au-based nanomaterials are most widely used for this purpose, owing to the following advantages it offers: 1) a strong X-ray attenuation 1960 capability that makes it suitable for use in computer tomography (CT) imaging contrast agent and radiosensitizer [43][44][45] ; 2) as it can be easily surface-modified and embedded in structures such as liposomes and polymer particles, it is frequently used in different tumor treatment protocols; 3) as an inert metal, it exhibits good biocompatibility and low biotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…39 As an alternative option, metal-based nanomaterials, especially high-Z materials (eg, Au, bismuth, platinum, gadolinium), have been used in experimental and clinical applications as common radiosensitizers. [40][41][42] Owing to the emission of low-energy photoelectrons and the interaction of Auger electrons, high-Z nanomaterials can absorb, scatter, and eradicate radiation energy. Moreover, when compared with other metal-based nanomaterials, Au-based nanomaterials are most widely used for this purpose, owing to the following advantages it offers: 1) a strong X-ray attenuation 1960 capability that makes it suitable for use in computer tomography (CT) imaging contrast agent and radiosensitizer [43][44][45] ; 2) as it can be easily surface-modified and embedded in structures such as liposomes and polymer particles, it is frequently used in different tumor treatment protocols; 3) as an inert metal, it exhibits good biocompatibility and low biotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Cationic gold nanoparticles can be combined with negatively charged nucleic acids and delivered to target cells. Some studies showed that the surface modification of AuNP can improve its stability, such as in cationic carbosilane dendrites ( Alle et al, 2022 ). It is possible to realize polygenic delivery of nanoparticles through LbL assembly technology.…”
Section: Inorganic-based Nanocarriers For Co-deliverymentioning
confidence: 99%
“…Tuy nhiên, xạ trị có thể gây ra tình trạng kháng lại của khối u và đòi hỏi liều bức xạ cao hơn để điều trị ở lần kế tiếp. Nhưng với liều điều trị cao này có thể gây ra tổn thương không muốn có cho các tế bào bình thường xung quanh mô khối u [51]. Do đó, để cải thiện độ hấp thụ bức xạ, các chất làm nhạy cảm bức xạ được đề xuất sử dụng nhằm làm tăng tổn thương cho các mô khối u trong khi giảm tổn thương cho các mô bình thường trong sử dụng liệu pháp RT.…”
Section: Aunps Trong Xạ Trị (Radiotherapy Rt) Và Liệu Pháp Quang Nhiệ...unclassified